2022
DOI: 10.1002/bse.3319
|View full text |Cite
|
Sign up to set email alerts
|

The role of green human resource management in the translation of greening pressures into environmental protection practices

Abstract: Corporate environmental sustainability requires two complementary types of green practices—environmental protection hardware (EPH) and environmental protection software (EPS). Stakeholder greening pressures drive implementation; however, corporate responses vary, often lacking the balance and intensity of EPS and EPH needed. This paper explores the role of green human resource management (GHRM) in explaining variations in the implementation of EPH and EPS in response to stakeholders' pro‐environmental pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 114 publications
1
16
0
Order By: Relevance
“…In doing so, we also respond to the many calls for studies to develop an understanding of the factors that support successful implementation of GSCM practices (Bianchi et al, 2021;De Burgos-Jiminez et al, 2014;Graham & McAdam, 2016;Longoni & Cagliano, 2015). Our results provide support for the vast majority of the mediated pathways between GSCM 2020) demonstrated partial rather than full mediation for the hypotheses under study (see also Vázquez-Brust et al, 2022). The authors argued that GHRM has an important background role to play in the aforementioned relationships and underline the importance of partial mediation, in comparison with studies that fail to establish such as relationship.…”
Section: Implications For Theorysupporting
confidence: 63%
See 1 more Smart Citation
“…In doing so, we also respond to the many calls for studies to develop an understanding of the factors that support successful implementation of GSCM practices (Bianchi et al, 2021;De Burgos-Jiminez et al, 2014;Graham & McAdam, 2016;Longoni & Cagliano, 2015). Our results provide support for the vast majority of the mediated pathways between GSCM 2020) demonstrated partial rather than full mediation for the hypotheses under study (see also Vázquez-Brust et al, 2022). The authors argued that GHRM has an important background role to play in the aforementioned relationships and underline the importance of partial mediation, in comparison with studies that fail to establish such as relationship.…”
Section: Implications For Theorysupporting
confidence: 63%
“…This finding supports Agyabeng‐Mensah et al (2020), who investigated the influence of internal GSCM practices and the mediating role of GHRM on supply chain cooperation and financial performance. More specifically, the relationships in the mediation analysis in Agyabeng‐Mensah et al (2020) demonstrated partial rather than full mediation for the hypotheses under study (see also Vázquez‐Brust et al, 2022). The authors argued that GHRM has an important background role to play in the aforementioned relationships and underline the importance of partial mediation, in comparison with studies that fail to establish such as relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study is a valuable addition to the literature on GHRM by integrating the two theories—signaling theory and AMO theory—within the green building context. Our study responds to Vázquez‐Brust et al's (2022) call to include the “opportunity” dimension of AMO theory in the GHRM literature. This was done by integrating signaling theory, where our study provided the significance of communicating an organizational commitment to employees through GHRM initiatives.…”
Section: Discussionmentioning
confidence: 62%
“…In terms of training, organizations focus on cultivating employees' sense of responsibility and enhance their communication skills with external stakeholders through various projects and opportunities, thus enhancing social recognition of the organization (Vázquez‐Brust et al. 2022). The social performance of employees is incorporated into the performance pay appraisal system to stimulate the motivation of employees to participate in social public welfare activities, enhance the adhesion between the organization and external stakeholders, promote mutual understanding between the organization and external stakeholders and thus enhance the legitimacy of the organization (Shepherd and Zacharakis 2003).…”
Section: Theory and Hypothesesmentioning
confidence: 99%